Service Productization for a South Karelian Riding School - Heinonen, Eve (Saimaan ammattikorkeakoulu, 2015)
The objective of the study was to productize a new service for a South Karelian riding school. New service ideas which would have the potential to attract new customer groups to local riding stables were innovated and the most potential suggestion was selected. Three case companies were chosen to represent different types of riding schools in the area. The companies were interviewed to gather data for evaluating the service ideas. The interviews were half-structured and they were carried out in person and via email correspondence. The outcome of the thesis was a service product for one of the case companies. Further development regarding pricing is needed to launch the product. Based on the study, the riding school entrepreneurs are interested in widening their service offerings.